Implementation Direct Cash Assistance of Village Funds (BLT DD) in Warnasari Village Sukabumi Districts Sukabumi Regency in 2021 - Sindy Amelia Puspita; Rizki Hegia Sampurna; Yana Fajar FY Basori (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The government's efforts to reduce poverty by enacting a number of policies. The government established a BLT DD policy during the Covid-19 pandemic to combat the poverty crisis induced by the Covid-19 outbreak. The purpose of this research is to find out how the direct cash assistance policy for village finances (BLT DD) is being implemented in Warnasari Village, Sukabumi District, Sukabumi Regency. This study uses a qualitative descriptive method, because the focus of the research studied is related to the implementation of BLT DD policies through the theoretical approach of Edward III (1980). Data collecting methods included observation, interviews, and document review. The researcher evaluated the data once it was obtained. Data analysis included data reduction, data presentation, and generating conclusions, as well as data validity (validation) through source triangulation and procedures. In this study, informants were chosen through purposive sampling, with a maximum of 8 participants participating. According to the findings of this study, the implementation of BLT DD in Warnasari Village was beneficial but not fully utilized because to budget restrictions and limited recipient quotas. Moreover, according to Edward III's theory, the implementation of BLT DD in Warnasari Village has been carried out well in terms of communication, resources, disposition, and bureaucratic structure; however, in terms of communication, Warnasari Village has not been able to socialize this policy optimally.